Apply the blended learning model in national defense and security education for university students in Viet Nam - Nguyen Linh Phong; Tran Tuan Canh; Ngo Gia Bao (International Journal of Evaluation and Research in Education (IJERE), 2026)
Despite the growing global consensus supporting the efficacy of blended learning, research remains scarce regarding its optimal application within specialized, practical disciplines like national defense and security education (NDSE) in Viet Nam higher education. This study addresses this empirical gap by analyzing the implementation, challenges, and impact of the blended learning model in NDSE for university students in Viet Nam. The study employed a mixed-methods design, encompassing a comprehensive literature review, the development of a theoretical model, and a quantitative survey of 312 students from several universities. Data were rigorously analyzed using structural equation modeling (SEM) to test the relationships among implementation factors, engagement, and learning outcomes. The findings indicate that technological infrastructure and digital competence are crucial preconditions for blended learning application, which enhances students’ interaction, learning interest, and ultimately, positive learning outcomes. However, limitations were identified, including insufficiently uniform technological infrastructure and the need to mitigate the increased workload for lecturers. These results provide broader policy implications for curriculum design, requiring targeted investment in IT infrastructure and systematic development of faculty digital literacy to effectively support the digital transformation of specialized military and security education in Viet Nam.